2015
DOI: 10.1002/mnfr.201500357
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs expression in normal and malignant colon tissues as biomarkers of colorectal cancer and in response to pomegranate extracts consumption: Critical issues to discern between modulatory effects and potential artefacts

Abstract: PE consumption appears to affect specific colon tissue miRs but surgery critically alters miRs levels hindering the discrimination of significant changes caused by dietary factors and the establishment of genuine differences between malignant and normal tissues as biomarkers. The components responsible for the PE effects and the clinical relevance of these observations deserve further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 49 publications
1
41
0
Order By: Relevance
“…Resveratrol, ellagic acid or green tea catechins [3,4,50] have been previously shown to modulate miRNA expression in certain tissues. We here provide additional evidence that HT, the foremost polyphenol of extra virgin olive oil and a unique component of the Mediterranean diet, also modulates the expression of miRNAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resveratrol, ellagic acid or green tea catechins [3,4,50] have been previously shown to modulate miRNA expression in certain tissues. We here provide additional evidence that HT, the foremost polyphenol of extra virgin olive oil and a unique component of the Mediterranean diet, also modulates the expression of miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Within this context, the potential role of plant-derived phenolic molecules (e.g. polyphenols) in miRNAs modulation is being very actively investigated [3][4][5][6]. As of now, however, there is no clear published evidence of a definite direct effect of a polyphenol on a specific miRNA.…”
Section: Introductionmentioning
confidence: 98%
“…The only study that has tried to link the urolithins with possible effects in human tissues was recently reported by Núñez‐Sánchez et al. . Despite a moderate modulation of various CRC‐related microRNAs in the colon mucosa of CRC patients following pomegranate intake, no association between colon tissue urolithins and the observed microRNAs changes was observed.…”
Section: In Vitro and In Vivo Effects Of Urolithinsmentioning
confidence: 99%
“…Another randomized, double blind, controlled trial investigated the effects of pomegranate extract (900 mg daily) on 35 CRC patients. They reported that pomegranate extract markedly modulates various microRNAs responsible for the colorectal cancer in colon tissue of CRC patients (Nunez‐Sanchez et al, ). In another study, 57 patients with recently diagnosed colorectal cancer received two types of pomegranate extracts (PE) daily until the programmed surgery; PE‐1 contained 72 mg/g punicalagin, 2 mg/g punicalin and 294 mg/g EA derivatives, and PE‐2 contained 155 mg/g punicalagin, 5.4 mg/g punicalin and 28 mg/g EA derivatives.…”
Section: Resultsmentioning
confidence: 99%